(untitled) (Orthopaedic SPOT, 2025)
Introduction: Our purpose was to evaluate the differences in metaglene positioning in deltopectoral and anterosuperior approach in total reverse shoulder arthroplasty. Methods: Patients who underwent total reverse shoulder arthroplasty for degenerative or traumatic pathology within a 10‐year period were selected. Two groups were created: group 1, deltopectoral approach; group 2, anterosuperior approach. The metaglene positioning was evaluated through anteroposterior radiography by the methods of Lévigne et al and Maurer et al. Statistical study was performed by Mann‐Whitney U‐test. Results: A total of 145 patients were admitted, 33 submited to deltopectoral approach and 112 anterosuperior. Surgery for degenerative pathology occurred in 106, for trauma in 39. The overall median age was 70 years (64‐75), in degenerative pathology 68 years (62‐72), in trauma 76 years (69‐81). Overhang showed no significant difference (p=0.882), 5.1±2.2 mm group 1 and 5.4±2 mm group 2. The tilt showed significant difference (p=0.005), 103.2±11o group 1 and 96.8±9.7o group 2. The beta angle showed significant difference (p=0.001), 81.4±7.3o group 1 and 74.6±8.6o group 2. When comparing traumatic and degenerative pathology, the overhang did not show significant difference (p=0.06), 5.8±1.6 mm traumatic pathology and 5.1±2.2 mm degenerative pathology. The tilt was signifi‐ cantly different (p<0.001), 104.8±10° traumatic pathology and 95.8±9.4o degenerative pathology. The beta angle was significantly different (zc wq <0.001), 82.5±6.6o traumatic pathology and 73.8±8.4o degenerative pathology. Conclusion: The approaches did not differ in the craniocaudal positioning of the metaglene, but tilt was lower in the anterosuperior approach and may correlate with future complications. Patients who had surgery for traumatic pathology showed greater inferior tilt of the metaglene.